Evolution of sensory neuropathy after initiation of antiretroviral therapy. Issue 3 (6th July 2017) - Centner, Chad M.; Little, Francesca; Van Der Watt, Johan J.; Vermaak, John‐Randel; Dave, Joel A.; Levitt, Naomi S.; Heckmann, Jeannine M.
ABSTRACT: Introduction: We studied the evolution of sensory neuropathy after antiretroviral therapy (ART) in human immunodeficiency virus–infected South Africans. Methods: Enrolment commenced before ART with 6‐monthly follow‐ups for 24 months. Symptomatic distal sensory polyneuropathy (SDSP) was defined as one symptom and sign. Symptom/sign scores were compared between visits. Results: We enrolled 184 participants. Pre‐ART, 16% had SDSP. After 18 months of ART, pain prevalence decreased in those with pre‐ART SDSP (odds ratio [OR], 0.09; 95% confidence interval [95%CI], 0.03‐0.29). Symptoms improved in 50% ever experiencing pain (mean improvement = 4.5 on 11‐point scale). Participants SDSP‐free pre‐ART developed SDSP at a rate of 18 per 100 person‐years. After 24 months ( n  = 102), 18% had SDSP. Stavudine (60% of cohort) did not predict incident SDSP, but associated with increased prevalence of reduced/absent reflexes at 18 months (OR, 2.24; 95% CI, 1.08‐4.65). Discussion: Painful symptoms improved during ART. Evolving sensory neuropathy was due to increasing small and large fiber dysfunction. Muscle Nerve 57 : 371–379, 2018